Early Rheumatoid Arthritis: Possibilities Of Mri Diagnosis - Ametova Alie Servetovna; Saitkulova Shahribonu Rakhmatillevna; Khaidarova Aziza Anvarovna (Zien Journals, 2022)
The article presents the results of a clinical and radiological examination of 65 patients with early rheumatoid arthritis with a duration of articular syndrome up to 12 months. The frequency of detection of erosions in standard radiography of the hands and magnetic resonance imaging (MRI) was analyzed depending on clinical and laboratory features. A standard examination protocol and image evaluation sequence have been developed. MRI is a more informative method for the topical diagnosis of early arthritis compared to standard radiography. In early rheumatoid arthritis, MRI made it possible to diagnose erosive changes in the joints in 36 patients out of 65, which is significantly more than with conventional X-ray examination (2 patients out of 65). Using MRI, erosive changes in the joints of the hands were diagnosed 12 months before their detection on radiographs, the most significant differences in the definition of destructive changes are observed in the area of the carpal bones and metacarpal heads. The frequency of detection of erosions in MRI of the hand correlated with seropositivity for antibodies to citrated proteins and did not depend on the activity of the process according to DAS28
Keywords: radiography standard; MRI; erosions; diagnostics